Kualitas Pelayanan Kesehatan Di Kabupaten Minahasa (Studi Kasus Pada Puskesmas Kawangkoan Kecamatan Kawangkoan Utara) - Siwi, Cynthia Maria; Moonik, Joutje (Tumoutou Social Science Journal, 2024)
This study aims to describe the Quality of Health Services at the Kawangkoan Health Center, North Kawangkoan District, Minahasa Regency using phenomenological qualitative research methods. Data collection techniques are observation, interviews and documents. The results showed that the health services provided by the Kawangkoan Health Center, North Kawangkoan District, Minahasa Regency were not optimal, the services were not in accordance with the SOP and did not meet the expectations of the community. It is still strongly felt by the community that the service process is not satisfactory because the service process is still convoluted. For this reason, it is recommended that services at the Kawangkoan Health Center, North Kawangkoan District, Minahasa Regency should provide services according to the SOP for the community. It is also necessary to pay attention to the Government in terms of facilities at the Health Center in order to add more equipment that is lacking so that it can smooth the process of health services for the community.